Identifikasi SMS Spam Menggunakan Metode Naive Bayes - Wahid, Abd; Baharulloh, Muhammad; Kahfiansyah, Raihan; Abrilianto, Taufik; Saifudin, Aries; Mulyati, Sri (Teknik Informatika Universitas Pamulang, 2021)
SMS (Short Message Service) or what we know as short message service, the use of SMS is still widely used among smartphone users. This short message service was created as a means of communication media that can be used to send digital messages to the people we want to address, just like sending regular messages, SMS users must have the intended address using the user's phone number. More and more SMS users, this is misused by irresponsible parties, one of the most common crimes committed by using short messages is a fraud that often occurs in the community, pornographic messages and besides that SMS spam is also very disturbing to the recipient. Identifying spam messages can be done by creating a filter on the message. The method used in this study uses the Naive Bayes algorithm by analyzing the words contained in the message to identify spam on spam services on smartphones.